Ocenjevanje in merjenje akutne pooperativne bolečine - Obran, Simona (Obzornik zdravstvene nege, 2000)
The treatment of acute postoperative pain is often not sufficient. Subjective nature of pain makes its evaluation complicated. However, for successful treatment, evaluation is absolutely necessary. Nowadays, evaluation and measurement of pain is gaining more attention and methods of measurement are being introduced into everyday clinical practice. Evaluation and measurement of pain is an important part of the work of a nurse treating a patient with pains. A nurse monitors patients condition all the time, communicates with him/her and gives psychological support. The article presents the results of aresearch work on acute postoperative pain, its evaluation and measurement. Aninquiry was carried out on expectations and experience related to treatment of pain. Pain was monitored, evaluated and measured for three days after surgery.
Keywords: Analgesia; Anesthesia; bolečina; Classification; merjenje; Nursing care; Pain measurement; Pain, postoperative; pooperativna bolečina; Therapy